De-westernisation, inter-Asian referencing and beyond. (February 2014) - Iwabuchi, Koichi
The necessity of de-westernising knowledge production has been widely advocated. This is especially pertinent with media and cultural studies, due to the rise of East Asian media cultures and their transnational circulation, hence a call for 'looking after Europe'. This article engages the issue by considering the possibility of inter-Asian referencing and the next steps to be taken. Inter-Asian referencing is a significant manoeuvre for making concepts and theories derived from Asian experiences translocally relevant and shared, as well as developing a nuanced comprehension of Asian experiences through reciprocal learning process. It is also significant for the study of East Asian media culture, as it has become an integral part of production and consumption of media culture in the region. The inter-Asian referencing project calls for researchers working both inside and outside of Asia to collaborate to develop the innovative production of knowledge and advance cross-border dialogue.